High-sensitivity piezoceramic elements for medical ultrasonic examination equipment - Spiridonov, N.A.; Gusakova, L.G.; Pogybko, V.M.; Spiridonov, V.N.; Ischuk, V.M. (Functional Materials, 2008)
Results of investigation for production of piezoelectric ceramic elements (PCE) with high values of piezosensitivity g₃₃ are discussed. Industrial materials ЦТССт-2М, ЦТС-46 based on the lead titanate-zirconate solid solutions were used for fabrication of PCE. Model solid solution Pb(Zr₀.₅₂Ti ₀.₄₈)O₃ (PZT 52/48) doped with various chemical elements was used, too. The advantage of semiceramic method for ceramic elements fabrication has been shown.